Vascular Adaptations in Pregnancy: The Critical Role of Endothelial Function and Nitric Oxide in Maternal-Fetal Health - Hina Riaz; Urooj Bhatti; Keenjher Rani; Afsheen Abro; Rabia Uqaili; Rubina Ahmdani (Pakistan Journal of Medicine and Dentistry)
Background: Endothelial dysfunction is a critical factor in hypertensive disorders of pregnancy, such as preeclampsia. This study aimed to evaluate the role of endothelial function, nitric oxide (NO), and endothelin-1 (ET-1) in normotensive and hypertensive pregnancies to understand the underlying vascular adaptations.